RELEVANCE COMPULSORY LEARNING IN BASIC EDUCATION, PANCASILA STUDENTS AND THE GOLDEN GENERATION OF INDONESIA IN 2045 - Fitri Silvia Sofyan; Aris Riswandi Sanusi (Journal Civics And Social Studies, 2023)
This study aims to determine the extent of the relevance between Compulsory Education in Basic Education 12 Years, Pancasila Students, and the 2045 Indonesian Golden Generation. The results of this study indicate that an educational strategy is needed to create the Indonesian Generation towards 2045 as a superior generation. Careful, well-planned strategy and integrated steps for all elements of the nation. In this case basic education is the foundation for seeking to improve the quality of human resources, "every citizen aged seven to fifteen years is obliged to attend basic education"[1]. The Pancasila Student Profile is designed according to the expectations or results of the Indonesian education system. As for what is meant by Pancasila Students, namely: "Indonesian students are lifelong students who are competent, have character, and behave according to Pancasila values"[2]. This statement is closely related to two things, namely: "the competence to become citizens of a democratic Indonesia and to become superior and productive human beings in the 21st Century". In this case, Indonesian students are expected to be able to participate in global development that is sustainable and resilient in facing various challenges.